2018
DOI: 10.1002/jctb.5658
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Shewanella oneidensis MR‐1 to the electrode material activated carbon fabric

Abstract: BACKGROUND Electroactive microorganisms generate current in microbial fuel cells by oxidizing organic compounds and transferring the electrons to an anode. Thereby the adsorption of cells to the electrode is the first step in the process of biofilm formation. RESULTS A comparison of different electrode materials showed that activated carbon fabric has the best cell adsorption properties for the simple and strong attachment of Shewanella oneidensis cells to the electrode material under aerobic and non‐electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…The activity of electrogenic microorganisms has a significant impact on the electrical performance of MFCs 12,25 . According to our work, the addition of SAs reduced the electrical production of MFCs, and production decreased with increased concentrations of SAs; this effect might be associated with the toxic effects of SAs on S. putrefaciens , 26 and these results were consistent with other reports 12,27‐29 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The activity of electrogenic microorganisms has a significant impact on the electrical performance of MFCs 12,25 . According to our work, the addition of SAs reduced the electrical production of MFCs, and production decreased with increased concentrations of SAs; this effect might be associated with the toxic effects of SAs on S. putrefaciens , 26 and these results were consistent with other reports 12,27‐29 …”
Section: Discussionsupporting
confidence: 92%
“…When SAs were added, the CV area was decreased, which might be due to decreased bacterial adhesion on the electrode surface 27 and the weakening of electron transfer from cell membrane to solid electrode via cytochrome c (DET) 32‐34 ; these results were confirmed by protein concentration and SEM analysis. Meanwhile, Figure 4c,d showed that the anode material could efficiently adsorb S. putrefaciens , which was consistent with the results of other similar studies 28 . Regarding MET, studies have shown that Shewanella strains can secrete soluble riboflavin, 18 which acts to mediate the electron transfer process 35 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to earlier studies, species of Shewanella MR-1 tend to self-attach to carbon based electrodes via hydrophobic anchoring from outer membrane lipoproteins. [35,36] Consequently, the differences in bacterial coverage between the two electrodes might be attributed to reduced anchoring for PE-DOT:PSS films, presumably due to the excess of hydrophilic PSS present on the surface of PEDOT:PSS, and enhanced binding to the PEDOT:PSS-PVA films, presumably due to hydroxyl groups at the PVA surface. [29] Finally, by using bright field microscopy we also confirmed the presence of the ΔmtrB mutant on both biased and control PEDOT:PSS-PVA gates, the former corresponding to the data shown in Figure 2a ( Figure S5, Supporting Information).…”
Section: Doi: 101002/advs202000641mentioning
confidence: 99%